2014
DOI: 10.4330/wjc.v6.i7.638
|View full text |Cite
|
Sign up to set email alerts
|

Calpain system and its involvement in myocardial ischemia and reperfusion injury

Abstract: Calpains are ubiquitous non-lysosomal Ca(2+)-dependent cysteine proteases also present in myocardial cytosol and mitochondria. Numerous experimental studies reveal an essential role of the calpain system in myocardial injury during ischemia, reperfusion and postischemic structural remodelling. The increasing Ca(2+)-content and Ca(2+)-overload in myocardial cytosol and mitochondria during ischemia and reperfusion causes an activation of calpains. Upon activation they are able to injure the contractile apparatus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 207 publications
0
54
0
2
Order By: Relevance
“…Microparticle derived PAF may be of particular importance in I/R since this powerful mediator activates platelets to promote their aggregation, adhesion to endothelial cells and leukocytes, and leukocyte sequestration in postischemic tissues. Calpain, a protease implicated in I/R, is also carried on these vesicular structures, which protects the enzyme from plasma inhibitors (413, 584). …”
Section: Plasma Membrane-derived Microparticlesmentioning
confidence: 99%
“…Microparticle derived PAF may be of particular importance in I/R since this powerful mediator activates platelets to promote their aggregation, adhesion to endothelial cells and leukocytes, and leukocyte sequestration in postischemic tissues. Calpain, a protease implicated in I/R, is also carried on these vesicular structures, which protects the enzyme from plasma inhibitors (413, 584). …”
Section: Plasma Membrane-derived Microparticlesmentioning
confidence: 99%
“…A review (Neuhof and Neuhof, 2014) recently demonstrated that calpain inhibition in animal experiments showed an enhanced tolerance towards ischemia (Neuhof et al , 2003), a reduction of myocardial infarction and reperfusion injury (Hernando et al , 2010; Khalil et al , 2005; Neuhof et al , 2008; Neuhof et al , 2004), and less remodeling (Ma et al , 2012). Other experiments have also shown neuronal preservation during ischemia with calpain inhibition (Nath et al , 2000).…”
Section: Pharmacologic Therapiesmentioning
confidence: 99%
“…Persistent activation of calpain proteases is another mechanism by which persistent hypotension leads to neuronal pathology (123). Calpains cleave the contractile components of vascular smooth muscles inhibiting their ability to contract (122). …”
Section: Chronic Effects Of Traumatic Brain Injurymentioning
confidence: 99%